The labor market experience and impact of undocumented workers - Julie L. Hotchkiss; Myriam Quispe-Agnoli (Federal Reserve Bank of Atlanta, 2008)
Using administrative data from the state of Georgia, the authors find that average wages among documented workers are lower in industries that employ undocumented workers and that a greater share of undocumented workers in those industries further lowers wages. In addition, undocumented workers have significantly lower labor supply elasticity, likely as a result of their limited employment and grievance opportunities. Furthermore, the inflow of undocumented workers does more to displace earlier hired undocumented workers than it does to displace documented workers.
Keywords: J61; J31; J42; F22; 330; immigration; wage impact; worker displacement